2016
DOI: 10.1248/bpb.b16-00316
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 24,24-Difluoro-1,3-<i>cis</i>-25-dihydroxy-19-norvitamin D<sub>3</sub> Derivatives and Evaluation of Their Vitamin D Receptor-Binding Affinity

Abstract: Fig. 1; also known as calcitriol) is the active hormonal form of vitamin D 3 (1); it regulates calcium and phosphorus homeostasis and exhibits potent antiproliferative activity.1-4) Its activity is regulated by the cytochrome oxidase P450 family member CYP24A1, which oxidizes 2 at the C24 and C23 positions to afford biologically inactive, side-chain-truncated, water-soluble end products.5-7) However, the metabolic stability of 2 can be increased by substitution of side-chain hydrogen with fluorine, which is ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Figure 25 (2015-2017) [337][338][339][340][341][342][343][344][345][346][347][348][349][350][351]. 1α,25-Dihydroxy-21-(3-hydroxy-3-methyl-1-methylenebutyl)vitamin D 3 (1428, UV1) [337] presented potent antitumoral effects over a wide panel of tumor cell lines without inducing hypercalcemia or toxicity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 25 (2015-2017) [337][338][339][340][341][342][343][344][345][346][347][348][349][350][351]. 1α,25-Dihydroxy-21-(3-hydroxy-3-methyl-1-methylenebutyl)vitamin D 3 (1428, UV1) [337] presented potent antitumoral effects over a wide panel of tumor cell lines without inducing hypercalcemia or toxicity in vivo.…”
Section: Resultsmentioning
confidence: 99%
“…In our effort to delineate VD 3 activity, we initially searched for VD 3 analogs that activate VDR but lack SREBP inhibitory activity. An in-house library of 250 vitamin D congeners was screened for their ability to inhibit the activity of an SREBP-responsive luciferase reporter, in which expression of luciferase is controlled by three SREBP binding sites. We found that a series of vitamin D analogs, bearing alkyltriazole and alkyltetrazole substituents at C2 ( 4 – 9 ) (Figure ), displayed limited SREBP inhibitory activities (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…However, biological assays of the corresponding triols 268 have shown poor binding to VDR. Nagasawa et al [109] also reported the synthesis of gem-24-difluoro-19-norvitamin D 3 derivatives of the same family (268, A = F), in order to evaluate their VDR binding affinity. In this case, the reaction between BT-sulfone 265 b and ketone 266 b with the aid of LiHMDS provided an equimolecular mixture of diastereomeric olefins 267 e in 92 % yield.…”
Section: Synthesis Of Vitamin Analogsmentioning
confidence: 99%
“…However, biological assays of the corresponding triols 268 have shown poor binding to VDR. Nagasawa et al [109] . also reported the synthesis of gem‐24‐difluoro‐19‐norvitamin D 3 derivatives of the same family ( 268 , A=F), in order to evaluate their VDR binding affinity.…”
Section: Synthesis Of Trisubstituted Alkenes Via Julia‐kocienski Olef...mentioning
confidence: 99%